Diagnostic exome sequencing in 100 consecutive patients with both epilepsy and intellectual disability - Snoeijen‐Schouwenaars, Francesca M.; van Ool, Jans S.; Verhoeven, Judith S.; Mierlo, Petra; Braakman, Hilde M. H.; Smeets, Eric E.; Nicolai, Joost; Schoots, Jeroen; Teunissen, Mariel W. A.; Rouhl, Rob P. W.; Tan, In Y.; Yntema, Helger G.; et al. (Epilepsia (Copenhagen), 2019)
Summary Objective Epilepsy is highly prevalent among patients with intellectual disability (ID), and seizure control is often difficult. Identification of the underlying etiology in this patient group is important for daily clinical care. We assessed the diagnostic yield of whole exome sequencing (WES). In addition, we evaluated which clinical characteristics influence the likelihood of identifying a genetic cause and we assessed the potential impact of the genetic diagnosis on (antiepileptic) treatment strategy. Methods One hundred patients with both unexplained epilepsy and (borderline) ID (intelligence quotient ≤ 85) were included. All patients were evaluated by a clinical geneticist, a (pediatric) neurologist, and/or a specialist ID physician. WES analysis was performed in two steps. In step 1, analysis was restricted to the latest versions of ID and/or epilepsy gene panels. In step 2, exome analysis was extended to all genes (so‐called full exome analysis). The results were classified according to the American College of Medical Genetics and Genomics guidelines. Results In 58 patients, the diagnostic WES analysis reported one or more variant(s). In 25 of the 100 patients, these were classified as (likely) pathogenic, in 24 patients as variants of uncertain significance, and in the remaining patients the variant was most likely not related to the phenotype. In 10 of 25 patients (40%) with a (likely) pathogenic variant, the genetic diagnosis might have an impact on the treatment strategy in the future. Significance This study illustrates the clinical diagnostic relevance of WES for patients with both epilepsy and ID. It also demonstrates that implementing WES diagnostics might have impact on the (antiepileptic) treatment strategy in this population. Confirmation of variants of uncertain significance in (candidate) genes may further increase the yield.